Quality assurance of scanned proton beams at different gantry angles using an ionization chamber array in a rotational phantom. (December 2022) - Decabooter, Esther; Roijen, Erik; Martens, Jonathan; Unipan, Mirko; Bosmans, Geert; Vilches-Freixas, Gloria
Highlights: Development non gantry mounted 'set-and-forget' QA procedure for 9 beam parameters. Freedom to measure at all gantry angles. The sensitivity is comparable to the scintillator detector. Measurement time is reduced by 40%. QA results over 12 months at our pencil beam scanning proton centre. Abstract: Purpose: To implement a single set-up monthly QA procedure for 9 different beam parameters at different gantry angles and evaluate its clinical implementation over a 12 month period. Methods: We developed a QA procedure using an array detector (PTW Octavius 1500XDR) embedded in a rotational unit (PTW Octavius 4D) at our proton facility. With a single set-up we can monitor field central axis position, field symmetry, field size, flatness, penumbrae, output, spot size, spot position and range at different gantry angles (AAPM TG 224). The set-up is irradiated with homogenous 2D fields with dynamic aperture and spot patterns at five gantry angles. A modular top is used to check the range consistency. Absolute γ analysis were performed to compare measured dose distributions to calculated dose. All other parameters are directly extracted from the measurements. Additionally, the sensitivity of the set-up to small changes in beam parameters were compared to the Lynx detector (IBA). Results: Over a 12 month period, output, symmetry, and flatness were within ± 2 %; FWHM, spot positions, penumbra widths, and central axis fields were within ± 1 mm. Range differences were all within 1/2 of the energy spacing (±0.6 MeV) relative to baseline. Most (2 %, 2 mm) γ-analysis showed agreement scores higher than 90 %. The sensitivity is comparable to the Lynx detector and measurement time is reduced by 40 %. Conclusion: The time-efficient monthly QA procedure that we developed can accurately be used to measure a large range of beam parameters at different gantry angles, within the TG 224 AAPM recommendations.